Morphogenesis of digitate structures in hot spring silica sinters of the El Tatio geothermal field, Chile. Issue 1 (30th September 2021) - Gong, Jian; Munoz‐Saez, Carolina; Wilmeth, Dylan T.; Myers, Kimberly D.; Homann, Martin; Arp, Gernot; Skok, John R.; van Zuilen, Mark A.
Abstract: In silica‐rich hot spring environments, internally laminated, digitate sinter deposits are often interpreted as bio‐mediated structures. The organic components of microbial communities (cell surfaces, sheaths and extracellular polymeric substances) can act as templates for silica precipitation, therefore influencing digitate sinter morphogenesis. In addition to biologic surface‐templating effects, various microenvironmental factors (hydrodynamics, local pH and fluctuating wind patterns) can also influence silica precipitation, and therefore the morphology of resulting digitate sinters. Digitate sinter morphology thus depends on the dynamic interplay between microenvironmentally driven silica precipitation and microbial growth, but the relative contributions of both factors are a topic of continuing research. Here we present a detailed study of digitate silica sinters in distal, low‐temperature regimes of the El Tatio geothermal field, Chile. This high‐altitude geothermal field is extremely arid and windy, and has one of the highest silica precipitation rates found in the world. We find that digitate silica sinters at El Tatio always accrete into the prevailing eastward wind direction and exhibit laminar growth patterns coinciding with day–night cycles of wind‐ and thermally driven evaporation and rewetting. Subaerial parts of digitate sinters lack preserved organics and sinter textures that would indicate past microbial colonization, while filamentous cyanobacteria with resistant, silicified sheaths only inhabit subaqueous cavities that crosscut the primary laminations. We conclude that, although fragile biofilms of extremophile micro‐organisms may have initially been present and templated silica precipitation at the tips of these digitate sinters, the saltation of sand grains and precipitation of silica by recurrent wind‐ and thermally driven environmental forcing at El Tatio are important, if not dominant factors shaping the morphology of these digitate structures. Our study sheds light on the relative contributions of biogenic and abiogenic factors in sinter formation in geothermal systems, with geobiological implications for the cautious interpretation of stromatolite‐like features in ancient silica deposits on Earth and Mars.